Wychowanie. Rewizja terminologii - Kowzan, Piotr (Kultura-Społeczeństwo-Edukacja, 2025)
In light of the critical perception of upbringing, dominant pedagogical literature fails to adequately address contemporary social challenges. This article analyses the weaknesses of traditional approaches to upbringing, particularly in terms of their autonomy from external political, social, and economic forces. Using Maton’s Legitimation Code Theory (LCT), I examine definitions of upbringing in terms of positional and relational autonomy. The findings suggest that most existing definitions of upbringing remain strongly influenced by external forces, which limits the autonomy of the discipline. This article proposes a critical revision of current concepts of upbringing and opens a discussion on the future of its autonomy in the context of contemporary social challenges.